CARBOHYDRATE DEGRADATION OF TUBER PASTE FLOUR BY THE ADDITION OF α-AMYLASE FROM TWO Lactobacillus SPECIES - Tatik Khusniati; Gadis Trieska Dewi; Anna P. Roswiem; Suci Ayu Azhari; Febi Ishfahani; Sulistiani Sulistiani (Jurnal Teknologi dan Industri Pangan, 2020)
The quality of Indonesia tuber flour can be improved by α-amylases which hydrolyzes the flour amylose to glucose and maltose. These monosaccharides causes the flour to have better homogeniety similar to wheat flour and easier to digest. This research aimed at investigating carbohydrate degradation of tuber paste flour by the addition of α-amylase from two Lactobacillus species. Lactobacillus species used were Lactobacillus bulgaricus and L. plantarum B110, while the flour types were made of local taro (Colocasia esculenta), gadung (Dioscorea hispida) and sweet potato (Ipomoea batatas), as well as wheat (Triticum) as a reference. Crude α-amylase activity and reducing sugars were detected by the Dinitrosalycylic acid (DNS) method. Data were statistically analyzed with ANOVA. Research results indicated that α-amylase from L. bulgaricus and L. plantarum B110 have been characterized for their optimum activity and stabilitiy. The reducing sugar content in taro, gadung, sweet potato paste flour and wheat paste flour added with α-amylase of L. bulgaricus increased by 0.008, 0.006, 0.004 and 0.001%, respectively. Meanwhile, the reducing sugars of the above flours added with amylase from L. plantarum B110, increased by 0.008, 0.008, 0.008, and 0.003%, respectively. Increase in reducing sugar contents in carbohydrate degradation of local tuber paste flour added with L. bulgaricus α-amylases was higher than that in wheat paste flour with a 0.001% increase. Similarly, the 0.008% increase of sugar content in tuber paste added with L. plantarum B110 α-amylase was also higher than that in wheat flour with 0.003% increase. Therefore, local tuber paste flour can be used as an alternative to wheat paste flour.